The Effects of Silica on Growth and Yield of Chrysanthemum Plants (Dendranthema Sp.) Cultivar Sheena and Snow White - Sylvatera Ayu Puspitasari; Didik Indradewa (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2019)
Silica is one of beneficial nutrient in plants. Silica functions to strengthen epidermal wall and vascular tissues so that it can affect the stems that are getting bigger and stronger. The present study was conducted to determine the effects of silica fertilizers on growth and yield of chrysanthemum plants in Sheena and Snow White varieties that have different anatomies. The present study used Split Plot Design. The main plot was the concentration of silica with 4 levels, i.e. 0 mg/l/m2, 31.1 mg/l/m2, 62.2 mg/l/m2, and 93.3 mg/l/m2. The subplots were two varieties, Sheena and Snow White. The present study revealed that Si fertilizers with 62.2 mg/L concentration could accelerate harvest age and the stem hardness in Snow White aged 45 days. The Snow White which has bark stem anatomy was more responsive to silica fertilizers than the Sheena with the woody stem anatomy. This research provides benefits for researchers, farmers and policy stakeholders to increased yield and quality for local and international market competition.